DEVELOPMENT OF FINAL STUDY MANAGEMENT SYSTEM BACKEND INTEGRATED SIA IN FACULTY OF ENGINEERING UNIVERSITY OF GENERAL SOEDIRMAN - Himawan Zidan Prayoga; Ipung Permadi; Swahesti Puspita R (Informatika, Universitas Jenderal Soedirman, 2022)
The system backend is the part that is responsible for managing applications and databases so that they can communicate with each other properly and smoothly in order to support the system interface to work according to its function. The backend of this system is used to be able to process final study data which includes final assignments to graduation from 5 users, namely bapendik as admin, head of department, final project commission, lecturers and students according to their respective duties. The purpose of this research is to build a Backend final study management system in the engineering faculty and a more efficient process of making final study files to facilitate the academic community in managing final study data so that it will improve the quality of academic services and can produce final study data more precisely, effectively. and efficient. The development of the Backend management system for this final study uses the DevOps method where the stages discussed in this research include the planning, development, implementation and use of the Laravel framework. The result of this research is that the backend of the final study management system can make it easier for all UNSOED Engineering faculties to manage all final study data and can already be accessed on the website browser.